Cotton flower metabolites inhibit SARS‐CoV‐2 main protease - Yufang Zhang; Wenkang Li; Yiming Hu; Tianze Ding; Muhammad Mubashar Zafar; Xue Jia; Liya Zhang; Maozhi Ren; Fuguang Li; Wenjing Wang (FEBS Open Bio, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been spreading globally for over 2 years, causing serious contagious disease and incalculable damage. The introduction of vaccines has slowed the spread of SARS‐CoV‐2 to some extent, but there remains a need for specific and effective treatment. The high chemical diversity and safety profiles of natural products make them a potential source of effective anti‐SARS‐CoV‐2 drugs. Cotton plant is one of the most important economic and medical crops and is the source of a large number of antiviral phytochemicals. In this work, we used SARS‐CoV‐2 main protein (Mpro) as the target to identify potential anti‐SARS‐CoV‐2 natural products in cotton. An in vitro assay showed that of all cotton tissues examined, cotton flower extracts (CFs) exhibited optimal inhibitory effects against Mpro. We proceeded to use the CF metabolite database to screen natural Mpro inhibitors by combining virtual screening and biochemical assays. We identified that several CF natural products, including astragalin, myricitrin, and astilbin, significantly inhibited Mpro with half‐maximal inhibitory concentrations (IC50s) of 0.13, 10.73, and 7.92 μm, respectively. These findings may serve as a basis for further studies into the suitability of cotton as a source of potential therapeutics for SARS‐CoV‐2.